Investigating the long-term co-movement and spillover effects of the stock markets between the United States and the ASEAN-5 countries for the periods up to and after the 2008 Global Financial Crisis and the COVID-19 pandemic - Calub, James Paul Misa (Animo Repository, 2022)
Financial integration has been an emerging trend in different countries’ financial markets. As such, these have strengthened ties between various nations economically especially for developed countries impact on smaller emerging nations. The United States has strong economic and financial ties with the ASEAN nations, however, if a developed country experienced a financial meltdown, how does this affect the status of the countries they are in a relationship with? This research seeks to explore the spillover effects and long-term co-movement of the United States stock market to the ASEAN-5 stock markets from 2007 to 2021 covering the 2008 Global Financial Crisis and the 2019 COVID-19 Pandemic. By using the daily closing prices of major stock index of US (S&P 500) and ASEAN-5 (JCI, FBM KLCI, PSEi, STI, & SET) from 2007 to 2021, various models were employed in order to gauge long-term co-movement and spillover effects. The research results show that there is indeed a significant effect coming from the S&P 500 to the ASEAN-5 stock market indices for the period up to the 2008 Global Financial Crisis and after. The PSEi received the highest spillover effect from the S&P 500 for the period up to the GFC and the STI for after the GFC. Furthermore, results show that the S&P 500 also received effects coming from the ASEAN-5 markets, notably from Malaysia (FBM KLCI) and Thailand (SET). Aside from that, a long-term co-movement is also observed between the markets involved in the study. However, the research on the COVID-19 poses limited results due to its on-going nature up to this day.